INDIRECT DETERMINATION OF AEROBIC POWER OF WOMEN PRACTITIONERS OF INDOOR CYCLING (Fiep Bulletin - online, 2014)
The indoor cycling (IC) is currently one of the most physical practice performed in gyms. Thus, the knowledge of the physiological responses of this sport practice is important. The aim of this study was to determine indirectly the aerobic power (VO2max) of women practitioners of IC during an incremental cycle Ergometer test performed at maximum and to compare the values of heart rate (HR) and subjective perception of effort (PSE) obtained during the test and a class of IC. Twelve apparently healthy women have participated in this study, all active physically and practitioners of RPM ® program for at least 12 months. We conducted a maximum incremental test cycle Ergometer cycling with 30W increments every two minutes until voluntary exhaustion. Later, the participants were followed during a lesson in ICI being monitored by CF and PSE at the end of each song. The average value of Vo2max found was 47 ml. kg. min -1 which was considered excellent for this sample. The average values of FCmax during the test and class were 185. 9 ± 10. 2 bpm and 176. 1 ± 2, 7bpm, respectively and the PSE was 17. 8 ± 3. 5 maximum for in class and 20.0 ±0.0 for the test. Therefore, we conclude that during the incremental test the participants reached higher values of FC and PSE, demonstrating a submaximal effort during the IC class, since the type of exercise is characterized as emphasizing the importance of interval workouts with varying intensity.
Keywords: maximal oxygen consumption; indoor cycling; subjective perception of effort